2017
DOI: 10.1590/1807-3107bor-2017.vol31.0094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of yttria-stabilized tetragonal zirconia polycrystal: Effects of different aging regimens

Abstract: This study aimed to characterize and compare the effect of different aging regimens on surface characteristic (topography and roughness), structural stability (phase transformation) and mechanical performance (Weibull analysis) of a Y-TZP ceramic. Discs (15 × 1.2 mm; VITA In-Ceram YZ) were prepared according to ISO 6872-2015 for biaxial flexural strength testing and randomly assigned into five groups (n = 30): as-sintered, no aging treatment (CTRL); 20 h in autoclave at 134°C, 2 bar pressure (AUT); intermitten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This material's high flexibility and other physical alterations in the face of aging procedures have also been tested. This affirmation proves this material's high resistance in an oral environment [41].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This material's high flexibility and other physical alterations in the face of aging procedures have also been tested. This affirmation proves this material's high resistance in an oral environment [41].…”
Section: Discussionsupporting
confidence: 66%
“…We analyzed yttria-stabilized tetragonal zirconia polycrystal and polymethyl methacrylate from a clinical perspective in two of the selected articles on which we based this research [ 38 , 39 , 40 , 41 , 42 ]. Bagegni A et al presented a complete meta-analysis, examining various implant-fixed restorations (interim or definitive) and their effect on implant survival.…”
Section: Discussionmentioning
confidence: 99%
“…Prior hydrothermal aging led to the highest monoclinic value of 75.27%, which is consistent with the present study. The slightly higher value could be due to the longer aging period in the autoclave of 20 h. A 1-year water storage at 37 °C used by Guilardi et al [47] The type of zirconia used in this study differed in the percentage of aluminum oxide and zirconia with higher aluminum oxide concentrations have been reported to resist the occurrence of monoclinic phase after aging [31]. However, the results of the present study showed comparable values for both zirconia generations, leading to acceptance of the null hypothesis and not supporting the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…A customized specimen holder device was used to ensure all specimens were placed in the same position for testing. Cemented crown specimens along with their bases were held in position in the loading device and subjected to 500,000 load cycles of 200 ± 50 N at 10 Hz [ 37 , 46 , 48 , 50 , 51 , 52 , 53 ]. The number of cycles used simulated a 2 year functional loading period in the mouth at an estimated rate of 240,000 cycles/year [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%